ELT ANALYSIS THROUGH LITERARY WORKS APPRECIATION - Hermayawati Hermayawati (Kajian Linguistik dan Sastra, 2010)
Literary works appreciation can be effectively used to master language competency beside as a means of intercultural understanding. The problem is, not everysecondary school’s teacher realizes it. That is why the writer intended to analysethe teachers’ teaching of English through learning of the literary works appreciation at the senior high school. It was a case study with teachers of English as thesubjects. The research object was the literary works appreciation learning process.The data were gathered by in-depth interviewing and documentation to analyse byusing McDonough McDonough model. This study found: there was only oneteacher who developed literary works appreciation, it needed 4 meetings with 90minutes for each, the learning materials were facilitated by the teacher, there wasonly one compulsory book to learn, i.e “Lorna and John”, and the activity aimedat assessing the learners’ speaking competence. The writer recommended: all teachers should teach literary works appreciation, develop learners’ appreciative behavior towards English literary works as a vehicle of adapting cultural discrepancies among foreigners, and schools should provide adequate English literary works.Key words: ELT, literary works, appreciation